DIALECTIC OF SPIRITUAL SPACE AND CULTURAL HERITAGE (Conferencea, 2023)
This article analyzes the issues of mutual dialectics of the concept of new spiritual space and national-cultural heritage. Priorities for creating a new spiritual space have been identified.